The photophysical properties of low symmetry phthalocyanines in conjunction with quantum dots - D'Souza, Sarah (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
he synthesis, extensive spectroscopic characterization and photophysical studies of low symmetry zinc phthalocyanine have been conducted. Comparisons have been made taking into consideration the influence of the solvent properties as well as substituent type and position. Photosensitizing properties of the zinc phthalocyanine derivatives in the presence of thiol capped CdTe quantum dots (QDs) were compared. The QDs were used as energy transfer donors and to facilitate with energy transfer through Förster resonance energy transfer (FRET) from the QDs to the MPcs. The linkage of unsymmetrically substituted 4-monoaminophenoxy zinc phthalocyanine (ZnAPPc) to CdTe quantum dots capped with mercaptopropionic acid (MPA), L-cysteine (L-cys) or thioglycolic acid (TGA) has been achieved using the coupling agents ethyl-N3 dimethylaminopropyl)carbodiimide (EDC) and N-hydroxy succinimide (NHS), which facilitate formation of an amide bond to form the QD-ZnAPPc-linked complex. The formation of the amide bond was confirmed using UV-Vis, Raman and IR spectroscopies, as well as AFM (atomic force microscopy). Förster resonance energy transfer (FRET) resulted in stimulated emission of ZnAPPc in both the linked (QDZnAPPc-linked) and mixed (QD:ZnAPPc-mixed) conjugates for MPA only. The linked L-cys and TGA complexes (QD-ZnAPPc-linked) gave the largest FRET efficiencies hence showing the advantages of covalent linking. Fluorescence quantum yields of QDs were decreased in QD:ZnAPPc-mixed and QD:ZnAPPc-linked. High triplet state quantum yields were obtained for the linked QD-phthalocyanine derivatives (ZnAPPc)and monoaminozinc phthalocyanine (ZnAPc) compared to when ZnAPPc and ZnAPc were mixed with MPA QDs without a chemical bond.
Keywords: Phthalocyanines; Photochemistry; Zinc; Quantum dots; Spectrum analysis; Nanoparticles